Enhanced photocatalytic activity of Al and Fe co-doped ZnO nanorods for methylene blue degradation. Issue 17 (1st December 2019) - Khalid, N.R.; Hammad, A.; Tahir, M.B.; Rafique, M.; Iqbal, T.; Nabi, G.; Hussain, M.K.
Abstract: Photocatalysis is a promising technique for the degradation of harmful organic dyes present in the waste water. Therefore, in this study Al, Fe co-doped ZnO (Al–Fe/ZnO) nanorods were synthesized via simple and cost-effective hydrothermal method. X-ray diffraction (XRD), scanning electron microscopy (SEM), and energy dispersive X-ray (EDX) showed that synthesized photocatalyst Al–Fe/ZnO has high crystallinity, nanorods-like morphology and compositionally pure. UV–visible absorption and photoluminescence (PL) spectroscopies were utilized to study the optical properties of samples. The results of UV–visible spectroscopy demonstrate that Al and Fe doping has decreased the band gap energy from 3.37 to 2.62 eV. This decrease in ZnO band gap allows it to absorb more photons for the excitation of valence band electrons and consequently, higher efficiency of the photocatalyst under light illumination. The PL results show that the doping of Al and Fe have played an efficient role to inhibit the recombination of electrons/holes pairs in ZnO during photocatalysis. Moreover, the visible-light driven photocatalytic efficiency of the samples was evaluated using methylene blue (MB) as model contaminant. It was observed that Al–Fe/ZnO photocatalyst exhibited seventeen (17) time higher degradation rate constant (k) for MB dye as compare to pure ZnO. This excellent photocatalytic activity of Al–Fe/ZnO sample could be attributed to rod-shaped morphology, improved visible light absorption and inhibited charge carrier's recombination due to synergistic effects of Al and Fe metal dopants.